Practical Experience of Operational Diagnostics and Defectoscopy on Photovoltaic Installations in the Czech Republic - Petr Mastny; Jan Moravek; Jiri Drapela (Energies, 2015)
Fundamental changes concerning the development of photovoltaic (PV) installations in the Czech Republic (CR) have occurred after 2010. The limits (and subsequent termination) of support for the newly installed PV power plants (cancellation of purchase prices for produced electricity) were the most important. This change of approach was advised by the relevant state authorities before the end of the year 2010 and resulted in a massive increase in PV installations during 2010. The goal of investors was to get more favorable conditions for the purchase of the electricity produced. A considerable amount of PV installations had been registered by the end of 2010, which do not reach the projected operating performance—this is caused by errors during installation and in many cases by inappropriately used (poor quality) components. This paper is focused on the operation of PV power plants in the conditions of the CR. A final analysis of the operational measurements performed and potential approaches and methods applicable to operational diagnosis of defects on PV panels are presented. A brief mention is also made of the economic situation of PV systems operating in the current legislative conditions in the CR.